Protective Effects of 1,8-Cineole Microcapsules Against Inflammation and Gut Microbiota Imbalance Associated Weight Loss Induced by Heat Stress in Broiler Chicken - Jiang, Zhihui; Luo, Maojun; Ma, Wentao; Ma, Shengming; Wang, Yao; Zhang, Kunpeng (Frontiers in Pharmacology, 2021)
Intestinal microbiota dysregulation is considered the primary trigger of low-grade inflammation responsible for weight loss due to heat stress. 1,8-Cineole is the major bacteriostatic agent in eucalypt and possesses remarkable anti-inflammatory properties. However, the mechanisms of its effect on intestinal microbiota remain unclear. In this study, 1,8-cineole was prepared into microcapsules prior to use as feed supplement in chickens. The microencapsulation efficiency and chemical stability of 1,8-cineole microcapsules were evaluated. The chicken treatment with 1,8-cineole microcapsules (1 or 3%) for 45 days, in the presence or absence of heat stress for fifteen days, commenced on Day 31, with or without an antibiotics mix (Abx) for three days on Day 27. Performance parameters were measured once a week from Day 30 through Day 45. Surface and entrapped concentration of 1,8-cineole was estimated as 7.89 g/100 g powder in the microcapsules. The time to maximal concentration (Tmax), terminal half-life (T1/2), and the area under plasma concentration-time curve (AUC0-t) of the encapsulated 1,8-cineole were higher than those of the nonencapsulated in treated chickens, although the maximal concentrations (Cmax) were similar. Chickens treated under higher temperatures with 1,8-cineole microcapsules exhibited lower levels of grade inflammation and higher body weight gain. Dietary 1,8-cineole microcapsules recovered the normal structure of upper ileum and altered the ratio of gut microbiota under heat stress and increased the ratio of Lactobacillus and Escherichia, whereas the proportion of Salmonella decreased based on 16S rRNA analysis of the upper ileum microbiota. In vitro, 1,8-cineole effectively inhibited the growth of Salmonella as demonstrated by inhibition zone assay. In summary, our findings elucidated the interaction between 1,8-cineole and intestinal microbiota as a new mechanism for the anti-heat stress effect of 1,8-cineole in preventing low-grade inflammation and weight loss. The results suggest that 1,8-cineole microcapsules may be a good feed supplement to protect against heat stress injury.